Liquidity as a Choice Variable: A Lesson from the Japanese Government Bond Market - Boudoukh, Jacob; Whitelaw, Robert F. (Review of Financial Studies, 1993)
In Japan, almost identical government bonds can trade at large price differentials. Motivated by this phenomenon, we examine the issue of the value of liquidity in markets for riskless securities. We develop a model of an issuer of bonds, a market maker, and heterogeneous investors trading in an incomplete market. We show not only that divergent prices for similar securities can be sustained in a rational expectations equilibrium, but also that this divergence may be optimal from the perspective of the issuer. Price segmentation is possible because agents have a desire to trade, but short-sale restrictions limit their trading strategies and prevent them from forcing bond prices to be equal. Restricting the form of market making to exclude price competition and unregulated profit maximization is also necessary to sustain price segmentation. The optimality of segmentation from the issuer's standpoint arises because of the issuer's ability to charge for the liquidity services provided to the investors.